Evaluating fundamental care knowledge to inform educational leadership. (25th April 2022) - Nowell, Lorelli; Davidson, Sandra; Gospodinov, Julia; Laing, Catherine; Shajani, Zahra; Dewell, Sarah; Conroy, Tiffany; Button, Didy
Abstract: Aim: To explore undergraduate nursing students' understanding of fundamental care and identify educational leadership opportunities to deepen students' understanding of fundamental care concepts. Design: Sequential‐explanatory mixed methods study. Methods: We conducted a cross sectional survey ( n  = 202) and focus groups ( n  = 24) to explore undergraduate nursing students' ability to identify fundamental care needs. All data were collected between November 2020 and April 2021. Survey data were analysed using descriptive and inferential statistics and focus group data were thematically analysed. Results: Year One students scored significantly lower in their ability to identify fundamental care needs compared with students in other years, even after controlling for route, gender and age. Post‐degree students scored significantly higher than direct entry or transfer students. Students ≤19 years of age had significantly lower scores compared with students ≥25 years of age. Our focus group findings highlighted that students were often unable to define fundamental care, but they identified learning about various components of fundamental care in a variety of ways. While students understood that fundamental care was required in all settings, they were challenged in providing this care in acute and virtual settings. Students shared several suggestions to support fundamental care skills development across the curriculum. Conclusions: There is a need for a clear definition and description of the fundamentals of care that is used consistently by faculty, students and curriculum documents. It is important to encourage and support educators to share real‐world nursing stories, offer students time to share their personal experiences, develop creative learning opportunities and foster student reflection to deepen students' understanding of the fundamentals of care. Impact: Educators need support to meaningfully incorporate fundamentals of care learning opportunities across multiple care settings. Educational leaders can use these findings to develop or adapt their curricula to support fundamental care skill development.